2012
DOI: 10.1371/journal.pone.0046441
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Gene Interaction and Functional Impact of Polymorphisms on Innate Immune Genes in Controlling Plasmodium falciparum Blood Infection Level

Abstract: Genetic variations in toll-like receptors and cytokine genes of the innate immune pathways have been implicated in controlling parasite growth and the pathogenesis of Plasmodium falciparum mediated malaria. We previously published genetic association of TLR4 non-synonymous and TNF-α promoter polymorphisms with P.falciparum blood infection level and here we extend the study considerably by (i) investigating genetic dependence of parasite-load on interleukin-12B polymorphisms, (ii) reconstructing gene-gene inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 124 publications
1
13
0
Order By: Relevance
“…Similar losses in diversity in immune defence genes associated with bottleneck events have been reported in other endangered vertebrates (Eimes et al 2011;Jamieson 2011;Basu et al 2012;Zhu et al 2013). The majority of heterozygous Seychelles warbler individuals have the rare variants observed, which suggests there may be a selective advantage with heterozygosity.…”
Section: Discussionsupporting
confidence: 71%
“…Similar losses in diversity in immune defence genes associated with bottleneck events have been reported in other endangered vertebrates (Eimes et al 2011;Jamieson 2011;Basu et al 2012;Zhu et al 2013). The majority of heterozygous Seychelles warbler individuals have the rare variants observed, which suggests there may be a selective advantage with heterozygosity.…”
Section: Discussionsupporting
confidence: 71%
“…If TLRs are involved in a co‐evolutionary arms race with pathogens, it is likely that balancing selection operates at these genes. This idea is also supported by the direct links that have been made between in vitro nucleotide variation at these genes with differential disease outcome (Basu et al ., ; Netea et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Modeling with MFOLD indicates that the C allele of this polymorphism prevents the binding of several transcription factors by altering the accessibility of the DNA (Basu et al 2012). In studies of malaria, this SNP has been associated with increased parasitemia, heightened severity of disease, and incidence of cerebral involvement (Basu et al 2012; Hananantachai et al 2007; Sinha et al 2008).…”
mentioning
confidence: 99%
“…Modeling with MFOLD indicates that the C allele of this polymorphism prevents the binding of several transcription factors by altering the accessibility of the DNA (Basu et al 2012). In studies of malaria, this SNP has been associated with increased parasitemia, heightened severity of disease, and incidence of cerebral involvement (Basu et al 2012; Hananantachai et al 2007; Sinha et al 2008). Case studies have found the minor allele G of this SNP to be associated with Crohn’s disease, asthma, decreased immunity after natural infection or vaccination against measles, and cancer-associated mortality (Dhiman et al 2008; Gallicchio et al 2008; Puthothu et al 2009; Sanchez et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation